2016
DOI: 10.1016/j.ejphar.2016.02.028
|View full text |Cite
|
Sign up to set email alerts
|

ORM-3819 promotes cardiac contractility through Ca2+ sensitization in combination with selective PDE III inhibition, a novel approach to inotropy

Abstract: This study is the first pharmacological characterization of the novel chemical entity, ORM-3819 (L-6-{4-[N'-(4-Hydroxi-3-methoxy-2-nitro-benzylidene)-hydrazino]-phenyl}-5-methyl-4,5-dihydro-2H-pyridazin-3-one), focusing primarily on its cardiotonic effects. ORM-3819 binding to cardiac troponin C (cTnC) was confirmed by nuclear magnetic resonance spectroscopy, and a selective inhibition of the phosphodiesterase III (PDE III) isozyme (IC50=3.88±0.3 nM) was revealed during in vitro enzyme assays. The Ca(2+)-sensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…As regards drug discovery and translational science in the field of acute cardiac care, the translational committee of the ESC-HFA issued some scientific bases [78] designed to pave the way towards the development of new agents but the preclinical field remains scarcely populated, with just some notable exceptions such as the calcium sensitizer/PDE inhibitor ORM-3819 [79,80].…”
Section: Some Views For the Futurementioning
confidence: 99%
“…As regards drug discovery and translational science in the field of acute cardiac care, the translational committee of the ESC-HFA issued some scientific bases [78] designed to pave the way towards the development of new agents but the preclinical field remains scarcely populated, with just some notable exceptions such as the calcium sensitizer/PDE inhibitor ORM-3819 [79,80].…”
Section: Some Views For the Futurementioning
confidence: 99%
“…The phosphodiesterase inhibitor and inodilator milrinone were indeed shown to interfere with the BKCa channels. 49 In a previous article, 22 we tested the PDE inhibitory effect of ORM-3819 on purified PDEIII and PDEIV isozymes and found that ORM-3819 is a very selective inhibitor of PDEIII, with a selectivity versus PDEIV of more than 12,000-fold. In comparison, such selectivity was 8000 for levosimendan 50 but only 14 for milrinone (see Table 2 on page 11 in de Cheffoy de Courcelles et al 51 ).…”
Section: Discussionmentioning
confidence: 99%
“…41 4-AP-sensitive potassium channels have been proposed to play a role in the vasomotor tone of coronary arteries under pathological conditions. 42 Both ORM-3819 and levosimendan have been shown to elicit beneficial hemodynamic effects in canine pathological cardiac models 22,43 and, in the case of levosimendan, in human severe heart failure. [44][45][46] The activation of voltage-gated potassium channels is significantly involved in the vasodilatory mechanism induced by ORM-3819.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations